answersLogoWhite
notificationBell

Top Answer
User Avatar
Wiki User
Answered 2010-08-03 07:17:30

8 3/9 - 5 2/3 = 2 2/3 (that is, two and two thirds).

001
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Your Answer

Related Questions


It is: 2/3 minus 2/9 = 4/9


Expressed as a proper fraction in its simplest form, 4/9 - 2/3 = -2/9 or minus two ninths.


9 ninths divided by 3 equals 3 ninths. 3 thirds divided by 3 is 1 third. 1 third equals 3 ninths. 2 thirds equals 6 ninths. 2 thirds is bigger


5/9 minus 2/3 equals -1/9


It is: 12 and 4/9 minus 1 and 2/3 = 10 and 7/9


To get ninths from thirds, you need to multiply both numerator and denominator by 32/3 = (2*3)/(3*3) = 6/9


1 third = 3 ninths, 3 ninths - 2 ninths = 1 ninth.


(2/3) / (-2/9) = (2/3)*(-9/2) = -3


The answer is 2/3 minus 2/9 = 4/9


Seven ninths minus four ninths is 1/3.


6 ninths. That is two thirds: 2/3.


2/3 = 6/9 They are equivalent fractions.


3 minus 2/3 is 2 1/3



6 minus 3 and two thirds = 2 and one third.



When subtracting 2/3 from 2/3, you will get an answer of zero.


10 and 11 ninths or 11 and 1 ninth


2 ninths 2/3=6/9 6/9 - 4/9 = 2/9


No, 2/3 is equivalent to 4/6.


1 - 2/3, first convert the 1 to thirds, thusly 3/3 - 2/3 = 1/3So, 1 minus two thirds equals one third.


4 2/3 - 2 = 2 2/3 or two and two thirds.


There are two thirds in two thirds, as two thirds suggests. Or the answer could be three if you look at it a different way. One third (1/3) of two thirds (2/3) is two ninths (2/9).



Expressed as a mixed number in its simplest form, 3 - 7/9 = 2 2/9 or two and two ninths.